3D/4D Geological Modeling for Mineral Exploration (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
With the development of high-precision geological observation technology, in situ mineral microanalysis technology, isotope geochemical analysis technology, deep geophysical exploration technology, deep drilling, real-time mining, remote sensing highresolution hyperspectral image technology, and supercomputer and industrial intelligence, geoscience has entered an era of big data and artificial intelligence in the 21st century. Three-dimensional/four-dimensional (3D/4D) geoscience modeling with the multi-disciplinary intersection of geosciences has been used as the basis for mineral exploration and the extraction of geosciences information for mineral resource assessment.